A study on success factors of government projects / Husna Norazimah Haji Hurairy - Haji Hurairy, Husna Norazimah (Faculty of Architecture, Planning and Surveying, 2013)
Construction of government project is helping in growth of economy. When to construct the project under the government, key of success factor will play an important role. The definition of success factor has determined differently by each party in construction team. The perception of success factor will always relate with time, cost and quality. The success factor of project can be seen through the project manager, project itself, project team, team organisation, external environment and the financial of the project. During the construction phase, there are many issues that can restrict the project to finish in schedule. The project will involve in such of situation such as extension of time, change order, progress payment and suspension, delay or interruption.